Faktor-Faktor yang Mempengaruhi Preferensi Pemilih Usia Muda dalam Pemilihan Presiden 2024 di Kota Medan menggunakan Regresi Logistik Biner - Husniyah, Nailuh; Tarigan, Enita Dewi Br.; Siringoringo, Yan Batara Putra (Pattimura Proceeding, 2024)
This study aims to identify factors that influence young voters' preferences in the 2024 presidential election in Medan City. There are 12 independent variables used in this study, namely socio-culture, age, education, track record, policy, political issues, political interest, campaign, social media, trust, candidate quality, and debate results. The dependent variable is voter preference, with a value of 0 for not voting and 1 for voting. This study used binary logistic regression method with purposive sampling technique to collect data from 271 respondents of young voters in Medan City. The results show that the independent variables jointly affect the dependent variable, as indicated by the G-test value of 85.909 which is greater than the value of χ_((0,05;12))^2(21.026). Through the Wald test, it is known that there are 6 independent variables that have a significant effect on the dependent variable, namely socio-culture (9.011), age (11.339), track record (4.638), political issues (4.403), campaign (4.165) and debate results (13.901), where these values are greater than the value of χ_((0,05;1))^2(3.841). While the remaining 6 variables, namely education (1.203), policy (0.072), political interest (1.435), social media (0.128), trust (1.557), and candidate quality (1.891) have no significant effect on the dependent variable, because the Wald test values of the six variables are smaller than the value of χ_((0,05;1))^2(3.841).